2021
DOI: 10.3390/agronomy11030579
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria Associated with a Native Solanaceae Promote Plant Growth and Decrease the Effects of Fusariumoxysporum in Tomato

Abstract: Plant growth-promoting rhizobacteria are often utilized to improve crop health and productivity. Nevertheless, their positive effects can be hindered if they fail to withstand the environmental and ecological conditions of the regions where they are applied. An alternative approach to circumvent this problem is a tailored selection of bacteria for specific agricultural systems. In this work, we evaluated the plant growth promoting and pathogen inhibition activity of rhizobacteria obtained from the rhizosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Sun et al . ( 2020 ) reported that Propionibacteriales have drought, salt tolerance, alkali resistance and stress resistance, in addition to strong degradation capabilities (Ivanova et al ., 2016 ), while Paenibacillaceae are plant growth promoter and biocontrol agents (Delgado‐Ramírez et al ., 2021 ). Cui et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al . ( 2020 ) reported that Propionibacteriales have drought, salt tolerance, alkali resistance and stress resistance, in addition to strong degradation capabilities (Ivanova et al ., 2016 ), while Paenibacillaceae are plant growth promoter and biocontrol agents (Delgado‐Ramírez et al ., 2021 ). Cui et al .…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Lysinibacillus enhanced the growth and yield of rice (Oryza sativa) under greenhouse conditions (Dhondge et al, 2021). Sun et al (2020) reported that Propionibacteriales have drought, salt tolerance, alkali resistance and stress resistance, in addition to strong degradation capabilities (Ivanova et al, 2016), while Paenibacillaceae are plant growth promoter and biocontrol agents (Delgado-Ramírez et al, 2021). Cui et al (2018) found that Micrococcaceae had strong effects on microbial N metabolism, and a member of the family Micrococcaceae isolated from halophytic rangeland plants could improve wheat productivity, especially the attributes related to seed and forage quality, under salinity stress conditions (Hajiabadi et al, 2021).…”
Section: Relationship Between Soil Microbe and Astragalus Plant Growt...mentioning
confidence: 99%
“…The antifungal behavior of endophytic bacteria could be attributed to the biosynthesis of numerous allelo-chemicals [73]. The impact on the disease severity and disease incidence at all the concentrations could be the result of the presence of some antimicrobial compounds such as phenazines, ammonia, pyrrolnitrin, hydrocyanic acid, and pyoluterorin [74]. In Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiosis largely refers to antimicrobial compounds and a huge number of antimicrobial compounds such as 2,4diacetylphloroglucinol (DAPG), oomycin A, phenazine, tropolone, pyoluterorin, hydrogen cyanide, pyrrolnitrin, tensin, amphisinand, and cyclic lipopeptides were produced by pseudomonads [64], while xanthobaccin, oligomycin A, zwittermicin A, and kanosamine were produced by Streptomyces sp., Stenotrophomonas sp., and Bacillus sp. [74]. The wilt prevalence in eggplant to an extent of more than 70% was reported to be contained by the formulations of Pseudomonas sp., Enterobacter sp., and Bacillus sp., and it was found that most of these isolates produced an antibiotic DAPG under in vitro conditions [75].…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth-promoting bacteria (PGPB) can be defined as microorganisms present in the rhizosphere that are able to develop harmonious interactions with plants, modulating their metabolism and stimulating their productivity [18,19]. PGPR can hold great potential for application in agriculture thanks to their direct plant-growth promotion abilities, being used as biofertilizers [20][21][22][23][24][25], phytostimulators [26][27][28][29] and rhizomediators (induction of the plant tolerance to contaminants) [30]. In addition, they stimulate tolerance to environmental stress, such as low soil fertility [31], heavy metal contents [32] or drought [33][34][35].…”
Section: Introductionmentioning
confidence: 99%